Past, Present, and Future: Performance of Two Bivalve Species Under Changing Environmental Conditions - Steeves, Laura E.; Filgueira, Ramón; Guyondet, Thomas; Chassé, Joël; Comeau, Luc (Frontiers in Marine Science, 2018)
Globally, the production of marine bivalves has been steadily increasing over the past several decades. As the effects of human population growth are magnified, bivalves help provide food security as a source of inexpensive protein. However, as climate change alters sea surface temperatures (SST), the physiology, and thus the survival, growth, and distribution of bivalves are being altered. Challenges with managing bivalves may become more pronounced, as the uncertainty associated with climate change makes it difficult to predict future production levels. Modelling techniques, applied to both climate change and bivalve bioenergetics, can be used to predict and explore the impacts of changing ocean temperatures on bivalve physiology, and concomitantly on aquaculture production. This study coupled a previously established high resolution climate model and two dynamic energy budget models to explore the future growth and distribution of two economically and ecologically important species, the eastern oyster (Crassotrea virginica), and the blue mussel (Mytilus edulis) along the Atlantic coast of Canada. SST was extracted from the climate model and used as a forcing variable in the bioenergetic models. This approach was applied across three discreet time periods: the past (1986-1990), the present (2016-2020), and the future (2046-2050), thus permitting a comparison of bivalve performance under different temporal scenarios. Results show that the future growth is variable both spatially and interspecifically. Modelling outcomes suggest that warming ocean temperatures will cause an increase in growth rates of both species as a result of their ectothermic nature. However, as the thermal tolerance of C. virginica is higher than M. edulis, oysters will generally outperform mussels. The predicted effects of temperature on bivalve physiology also provided insight into vulnerabilities (e.g. mortality) under future SST scenarios. Such information is useful for adapting future management strategies for both farmed and wild shellfish. Although this study focused on a geographically specific area, the approach of coupling bioenergetic and climate models is valid for species and environments across the globe.